The Impact of Consumer Behavior on the Formation of Sustainable Development Strategies of Companies in the Context of Digitalization and Virtualization - Zulfiya Arynova; Saida Kaidarova; Dana Bekniyazova; Svetlana Zolotareva; Valentina Shelomentseva; Saltanat Zhanuzakova; Alma Mussina (Qubahan Academic Journal)
Market shifts such as the growth of the urban middle class and the increasing number of women in the labor force are changing consumer habits, while the rise in education and digital literacy has expanded consumer engagement online. The article presents a conceptual model of interaction between consumers and companies in a virtual environment that ensures the effective implementation of sustainable development principles in business processes. The purpose of this study is to develop and empirically validate a conceptual model of consumer-company interaction in the digital environment that facilitates corporate adaptation to sustainability demands. To achieve this, a mixed-methods approach was used, including an expert survey and correlation analysis of 50 companies. The results demonstrate a statistically significant relationship between virtual consumer activity and companies' sustainability indicators, confirming the model’s relevance and predictive potential. The study concludes that informed and active consumers play a transformative role in shaping sustainable business strategies in the context of digitalization and labor market evolution.